Dysphagia in Patients with Neck Dissections - Mihaylova, Zornitsa (International Journal of Scientific Research and Management (IJSRM), 2019)
A common complication in patients with malignancies in the maxillofacial and cervical area is the impaired swallowing, due to the progress of the neoplasm or as a result of the treatment applied. Operative methods for the management of malignancies in the maxillofacial and cervical areas may damage anatomical structures, therefore causing swallowing disorders.The purpose of the present study is to determine the degree of involvement of the swallow function depending on the volume of surgery - neck dissection.Methods: SSQ (Sydney Swallowing Questionnaire) tool was used to assess the presence of dysphagia in operated patients, as well as an impaired swallowing function. The results obtained were analyzed by SPSS Vers23.0.        Results. Prospectively longitudinal study included 68 patients (25 women and 43 men) at mean age of 61.18 years (SD - 13.66). The reliability of the SSQ tool is assessed via Cronbach's coefficient alpha α = 0.871, and the validity of the sample is calculated using the Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO coefficient) - 0.857. In the postoperative period, no significant difference in dysphagia was found in terms of the volume of surgery - neck dissection.            Conclusion. The type and the volume of neck dissection has no effect on the postoperative speech disorders and swallowing.